Extraction and Chemical Composition Analyses of Intracellular and Extracellular Polysaccharides from Trametes lactinea Liquid Fermentation - Yijun Liu; Lu Shen; Mei Yang; Kaitai Yang; Fei Cheng (Fermentation, 2024)
Trametes lactinea is a macrofungus commonly found on broadleaf tree felling piles with rich bioactivity, and its main active substances are polysaccharides, which have a certain medicinal value. Few studies have been conducted on the simultaneous study of intracellular and extracellular polysaccharides of fermented mycelia in liquid culture. In this study, T. lactinea collected from Eucalyptus stumps was subjected to liquid fermentation culturing and the extraction of intracellular and extracellular polysaccharides from the mycelium was optimized using unidirectional and orthogonal test methods. The intracellular and extracellular crude polysaccharides were isolated and purified, and polysaccharide fractions were obtained and assayed for their chemical composition. The main findings of this study are as follows: (1) The optimal conditions for the extraction of intracellular polysaccharides from T. lactinea mycelium were a material–liquid ratio of 1:40, an extraction temperature of 100 °C, a time of 5 h, and four repeats, wherein the polysaccharide extraction rate reached 5.1%. The optimal extraction conditions for the extracellular polysaccharides were a concentration ratio of 5:1, a concentration temperature of 70 °C, an ethanol concentration of 100.0%, and an alcohol settling time of 12 h. The polysaccharides could thus be extracted up to 0.63 mg/mL. (2) The intracellular and extracellular crude polysaccharides of T. lactinea mycelium were successfully isolated and purified, resulting in three homogeneous fractions of intracellular polysaccharides (IP-1, IP-2, and IP-3) and two homogeneous fractions of extracellular polysaccharides (EP-1 and EP-2). (3) The polysaccharide chemical composition resulted in the highest total sugar content of EP-1. IP-3 had the highest uronic acid content. The results of the monosaccharide composition analysis showed that the mycelial intracellular polysaccharides IP-1, IP-2, and IP-3 were all highest in glucose. Both IP-2 and IP-3 contained guluronic acid and glucuronic acid. Mannose was the most abundant extracellular polysaccharide in both EP-1 and EP-2. This study provides theoretical and technical bases for the comprehensive development and utilization of T. lactinea polysaccharides.